Association between clinical condition and F-waves changes in the acute phase of stroke - Luvizutto, Gustavo Jose [UNESP]; Bertotti, Marcelo Fernando Zeugner [UNESP]; Fernandes, Thiago Dias [UNESP]; Carvalho Nunes, Hello Rubens de [UNESP]; Braga, Gabriel Pereira [UNESP]; Bazan, Rodrigo [UNESP]; Lima Resende, Luiz Antonio de [UNESP] (Assoc Arquivos Neuro- Psiquiatria, 2016)
Objective: To relate F-waves with clinical and Laboratory exams in the acute phase of stroke. Methods: Inclusion criteria for this crosssectional study were: hemiplegia, absence of previous cranial trauma, myopathy, diabetes, alcoholism or other known causes of peripheral neuropathy, and normal sensory and motor conduction. The National Institutes of Health Stroke Scale (NIHSS) score, glycemia, glucositate hemoglobin, and CPK were obtained at admission by routine blood exams. After hospital admission, the F-wave latencies and persistence were obtained from the deep peroneal nerve using symmetrical techniques. Results: Evaluation of 20 individuals mean - age 66 years, 50% mate and 85% Caucasian - showed association of F-wave persistence with glycemia (r = 0.71; p < 0.001) and NIHSS categorized (NIHSS 1-7 = 65.0 x NIHSS 9-23 = 100; p = 0.004). Multivariate analysis found only association of F-wave persistence with glycemia beta = 0.59 (0.44-0.74); p < 0.001. Conclusion: The increase in the persistence of F-waves are associated with hyperglycemia in the acute phase of stroke.
Keywords: stroke; brain waves; electrophysiology